Influence of ergonomic factors on the productivity of man-machine system in mechanized forest harvesting - Schettino, Stanley; Minette, Luciano José; Soranso, Denise Ransolin; Lima, Roldão Carlos Andrade [UNESP] (Instituto de Pesquisa e Estudos Florestais (IPEF), 2022)
Aiming to evaluate the man-machine system in order to verify the influence of ergonomic factors on the set productivity, three harvesters and three forwarders models were selected, in a Brazilian forest company. The productivity data of the machines was compiled from the monthly operational reports of the company's activities, from January to December 2018. The machines were evaluated according to the Ergonomic Guidelines for Forest Machines from the Swedish Forestry Research Institute. To assess the ergonomic risk of activities for machine operators, the TOR-TOM index was used, which considers the Real Occupancy Rate (TOR) and the Maximum Occupancy Rate (TOM) during the course of their activities. The results showed that the average productivity of the machine sets was below the planned level. A strong negative correlation was found between the productivity of the system and the ergonomic parameters of the machines and activities, without interference from the age of the machines and the time of experience of the operators. The evaluated machines presented deficient ergonomic standards in almost all aspects evaluated, indicating that, when operating in unfavorable soil and climate conditions, they present ergonomic risks to their operators. The result of the TOR-TOM index for the operating activities of both machines clearly indicates a work situation with an ergonomic risk present, without optimum utilization of the workforce, resulting in losses in system productivity. It is concluded that there is a strong influence of ergonomic factors on the productivity of the man-machine system in forest harvesting activities.
Influência de fatores ergonômicos na produtividade do sistema homem-máquina na colheita florestal mecanizada
Keywords: Forest mechanization; Forestry operations; Forestry work organization; TOR-TOM index; Worker's health